Stumbling towards Empire: The Shanghai Local Post Office, the Transnational British Community and Informal Empire in China, 1863–97. Issue 3 (4th May 2018) - Harris, Lane J.
ABSTRACT: In the second half of nineteenth century, a small transnational British and foreign community grew up in the treaty ports scattered along China's coast, a community literally caught between the great inner Asian empire of the Manchu Qing and British-dominated informal empire in Asia. Although scholars often contend that few major developments occurred in the foreign sector of the treaty port world until the very end of the nineteenth century, this article joins recent revisionist scholarship seeking to better understand the growth of this transnational treaty port community through a study of the Shanghai Municipal Council's local post office in the context of informal empire prior to the rise of muscular Chinese nationalism in the early twentieth century. As an institutional history of the virtually unknown local post office, this article is a study of the decades-long process by which the foreign settler community of Shanghai slowly built up the administrative capacity, trading networks and communications infrastructure of informal empire and semi-colonial order in the nineteenth-century treaty ports. The history of the local post office is largely unknown not because of its insignificance, but because we have not paid enough attention to the institutions that facilitated the emergence of transnational expatriate and settler communities throughout the world of British informal empire and the global and local influences that shaped them.